Sustainable management of copper-contaminated soils using vetiver root biochar - Sameer Neve; Dibyendu Sarkar; Zhiming Zhang; Rupali Datta (BMC Chemistry)
Abstract Throughout the 19th and early 20th centuries, copper mining was a predominant industry in Michigan’s Upper Peninsula, resulting in substantial environmental issues due to the generation of mining waste. This waste, referred to as stamp sands, was disposed of in Lake Superior, causing severe harm to aquatic ecosystems. Later, the stamp sands were dredged and deposited along the lake shores, causing large-scale contamination with copper. This rendered the land incapable of supporting vegetation. This study investigates the efficacy of vetiver (Chrysopogon zizanioides) root biochar as a soil amendment to enhance the quality of copper-contaminated stamp sands. The biochar was produced from spent vetiver roots following essential oil extraction, using a circular economy approach. Biochar was incorporated with the stamp sand at various concentrations (0%, 2.5%, 5%, 10%, 20% w/w) and incubated over a 60-day period. Comprehensive soil analysis was conducted to assess carbon, nitrogen, phosphorus, organic matter, and copper speciation due to the amendments. The results indicated significant improvements in water-holding capacity, alkalinity, electrical conductivity, nutrient content, and organic matter levels. The 20% biochar amendment had a significantly higher impact on all parameters as compared to the other amendment rates. Geochemical fractionation of amended soil showed that Cu was predominantly in bound forms, thereby reducing its bioavailability. These findings indicate that vetiver root biochar can improve soil quality and potentially facilitate vegetation growth in contaminated Superfund sites integrating principles of circular economy for sustainable management of resources.